Is severe hypocalcemia immediately life threatening?. Issue 10 (October 2018) - Duval, Maxime; Bach-Ngohou, Kalyane; Masson, Damien; Guimard, Camille; Le Conte, Philippe; Trewick, David
Abstract : Objective: Severe hypocalcemia (Ca <1.9 mmol/L) is often considered an emergency because of a potential risk of cardiac arrest or seizures. However, there is little evidence to support this. The aim of our study was to assess whether severe hypocalcemia was associated with immediately life-threatening cardiac arrhythmias or neurological complications. Methods: A retrospective observational study was carried out over a 2-year period in the Adult Emergency Department (ED) of Nantes University Hospital. All patients who had a protein-corrected calcium concentration measure were eligible for inclusion. Patients with multiple myeloma were excluded. The primary outcome was the number of life-threatening cardiac arrhythmias and/or neurological complications during the stay in the ED. Results: A total of 41, 823 patients had protein-corrected calcium (pcCa) concentrations measured, 155 had severe hypocalcemia, 22 were excluded because of myeloma leaving 133 for analysis. Median pcCa concentration was 1.73 mmol/L (1.57–1.84). Seventeen (12.8%) patients presented a life-threatening condition, 14 (10.5%) neurological and 3 (2.2%) cardiac during ED stay. However, these complications could be explained by the presence of underlying co-morbidities and or electrolyte disturbances other than hypocalcemia. Overall, 24 (18%) patients died in hospital. Vitamin D deficiency, chronic kidney disease and hypoparathyroidism were the most frequently found causes of hypocalcemia. Conclusion: Thirteen percent of patients with severe hypocalcemia presented a life-threatening cardiac or neurological complication on the ED. However, a perfectly valid alternative cause could account for these complications. Further research is warranted to define the precise role of hypocalcemia.